Assessing the Legal Impact of Halal Certification Obligations Through the Lens of Social Awareness and Consumer Rights Protection - Denha, Boorahan; Ummah, Shofiyatul; Rahmawati, Ai; Ridho, Ali; Harahap, A Aziz (Graduate School of UIN Syarif Hidayatullah Jakarta, 2024)
Halal certification aims to meet specific standards and gain legal recognition for products as per Indonesia's 2014 Halal Product Assurance Law. It represents a social responsibility for producers. Despite administrative registration, violations of halal certification can disrupt public order and are considered criminal offenses. The study uses a normative-empirical method, combining literature reviews and Gustav Radbruch's legal theory. Results show that mandatory halal certification under the Job Creation Law has raised awareness about halal consumption, especially among entrepreneurs. However, procedural obstacles like insufficient review and delays persist. The law has provided legal certainty and consumer rights protection. To improve halal certification services, uniform education from the Halal Product Assurance Agency (BPJPH) is recommended, focusing on small and medium-sized enterprises (UMKM).